PENGARUH PARTISIPASI ANGGARAN, ASIMETRI INFORMASI, LOCUS OF CONTROL, PENEKANAN ANGGARAN, DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP SENJANGAN ANGGARAN (STUDI EMPIRIS PADA SKPD KABUPATEN BENGKALIS) - Dwi Untari; Azwir Nasir; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Purposes this study was aims to look at the effect of budgetary participation, information asymmetry, locus of control, suppression budgets, and environment uncertainty towards budgetary slack in Bengkalis regency. The population in this study was 28 SKPD in Government Bengkalis. The first hypothesis testing results show that budget participation variables significantly influence budgetary slack. The second hypothesis testing results show that information asymmetry variables significantly influence budgetary slack. The third hypothesis testing results show that the locus of control variables significantly influence budgetary slack. The fourth hypothesis testing results indicate that the suppression of variables significantly influence the budget budgetary slack. The fifth hypothesis testing results show that the environment uncertainty variables significantly influence budgetary slack. Rated R Square of 0.820 (82%). It explains that the budgetary slack influenced by budgetary participation, information asymmetry, locus of control, suppression budgets, and the uncertainty of the environment, while 18% more-facto influenced by other factors not examined in this study.Keywords : Budgetary participation, information asymmetry, locus of control, suppression budgets, environment uncertainty, budgetary slack